Handout sebagai Perangkat Pembelajaran Praktis - Wayan Mahardika Prasetya Wiratama (Fakultas Teknik Universitas Negeri Malang, 2019)
This learning device development was based on the observation at Public Vocational High School 3 Singaraja where the problems that occurred were 1) students only waited for teachers’ explanation, and 2) no applicative material that made the learning process difficult. The subject of this research and development was Basic Electricity and Electronic teacher from the class of X-TITL 1 in Public Vocational High School 3 Singaraja and its 35 students. The product testing was performed in two stages: 1) limited test, and 2) implementation test. The data instruments were validation and observation sheets, where the measurement aspect from the data collection was learning device validity and learning device practicality. The handout validation results obtained 80.6 percent score, the observation sheet of learning device implementation got 87.5 percent score, and the observation sheet of teacher’s activity obtained 92.6 percent score. The practical test of learning device was based on the analysis and observer assessment on the observation sheet of a learning device and teacher’s activity. The total percentage of learning activity was 80.4 percent (70 percent is less than PR is less than 85 percent), or a good category. The total percentage of teacher activity was 80.8 percent (70 percent is less than PG is less than 85 percent) or an active category. Thus, from two observations above, it could be stated that the learning device met the practicality criteria.Keywords: handout, valid, practical